Patient safety culture regarding intravenous therapy in Guangzhou, China: a cross-sectional survey - Ji Cui-Hong; Xu Fei-Hua; Pan Shan (Sciendo, 2019)
To investigate the patient safety culture regarding intravenous therapy in parts of tertiary hospitals in Guangzhou, China.